Análise sobre padrões de relacionamentos amorosos no livro Sex and The City - Pastana, Marcela; Maia, Ana Cláudia Bortolozzi; Maia, Ari Fernando [UNESP] (My University, 2010)
The researches on sexuality, especially from Foucault’s critical analysis, have been denouncing that the sexual repression also happens through the patterns that suggest a fixed happiness model to be followed, not considering the autonomous development of the subject. The aim of this descriptive-qualitative study was to make a critical analysis of the content of the book Sex and The City, which presents narratives about sexual and love relationships in New York. This analysis evidenciated the reproduction of outdated sexual concepts presented on the following thematic categories: (1) Comprehension of the single woman as lonely and unhappy; (2) Comprehension of the single woman as independent and consumerist; (3) Comprehension that the single woman needs a heterosexual relationship related to the happy romantic ideal; (4) Comprehension of the love relationships as commodities: people as objects of use and exchange. The sexual and love patterns presented by the book demonstrate the repression reproduced uncritically by the mass culture. The Psychology has been an important area of the science to denounce the control of the sexuality from these perverse and ideological patterns.

As pesquisas sobre sexualidade, especialmente a partir da crítica foucaultiana, têm denunciado que a repressão sexual se faz também pelos padrões que sugerem um modelo fixo de felicidade a ser seguido e que desmerecem o desenvolvimento autônomo do sujeito. Este estudo qualitativodescritivo teve por objetivo realizar uma análise de conteúdo do livro Sex and the City, que narra relações sexuais e amorosas na cidade de Nova York. Essa análise evidenciou a reprodução de estereótipos sexuais vigentes, apresentados nas categorias temáticas: (1) Compreensão da mulher solteira como solitária e infeliz; (2) Compreensão da mulher solteira como independente e consumista; (3) Compreensão de que a mulher solteira é carente de um relacionamento heterossexual associado ao ideal romântico e feliz; (4) Compreensão dos relacionamentos amorosos como mercadorias: as pessoas como objetos de uso e troca. Os padrões sexuais e amorosos apresentados pelo livro demonstram a repressão reproduzida pela cultura de massas, acriticamente. A Psicologia tem sido uma importante área da ciência a denunciar o controle da sexualidade com base nesses perversos padrões ideológicos.
Keywords: sexual repression; love relationships; gender; repressão sexual; relacionamentos amorosos; gênero